The initial psychometric evaluation of a new Emergency Department Patient-Reported Experience Measure (ED PREM) - Claudia Bull; Julia Crilly; Sharon Latimer; Emma Hall; Brigid Gillespie (The Beryl Institute, 2023)
Patient-reported experience measures (PREMs) are critical to evaluating the person-centeredness, safety, and quality of healthcare services internationally. The aim of this study was to describe the initial psychometric evaluation of a new Emergency Department (ED) PREM. Adult patients presenting to the ED of a tertiary hospital in southeast Queensland, Australia during January 2022 were recruited in-person. Participants selected their preferred ED PREM mode of administration from online, telephone, or postal, and had 14 days from recruitment to complete the survey. Item reduction, structural validity, discriminant validity, and internal consistency reliability were assessed. A sample of 349 (68.4%) was achieved. Item reduction analysis indicated ceiling effects for all ED PREM items (ranging between 34.4-79.7%). Exploratory factor analysis revealed a 4-factor solution comprising 26-items that explained 55% of model variance. Cronbach's α ranged between 0.84-0.97 per factor, demonstrating internal consistency reliability. Known groups analysis demonstrated the ED PREMs' ability to discriminate experiences based on gender, age, and ED length of stay. The ED PREM is a valid and reliable instrument for capturing patient experiences in the ED. The content of the ED PREM emphasizes person-centeredness and shared decision making, making it suitable for use in clinical practice evaluation and health service performance measurement. The factor structure of the ED PREM should be confirmed in future research, and item redundancy addressed. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.